Penyuluhan dan Simulasi Menentukan Tipe dan Dosis Latihan Fisik yang Benar untuk Mencapai Kebugaran Fisik yang Optimal pada Pegawai Rektorat Universitas Mataram: Physical exercise; Type of physical exercise; Dose of physical exercise; Physical fitness - Gede Wira Buanayuda; Ida Bagus Alit; Ida Ayu Eka Widiastuti; Rifana Cholidah (Universitas Mataram, 2021)
One of the efforts made to get a healthy condition is to do regular physical exercise. Regular and measurable exercise will result in optimal physical fitness. Physical exercise is done regularly, according to the needs of each individual and by applying the basic principles of exercise, various benefits will be obtained for the body. The purpose of this activity is to educate and increase target knowledge in determining the type of physical exercise and preparing the correct dose of physical exercise to achieve optimal physical fitness. The participants were the Rectorate Staff of the University of Mataram, totaling 40 people, consisting of 14 men and 26 women. The activity lasted for approximately 120 minutes, located in the Ruang Sidang Utama of the Rectorate of the University of Mataram. The implementation of the activity consists of 5 stages, namely: (1) pretest, (2) delivery of counseling material, (3) simulation of determining the type and dose of physical exercise, (4) discussion, and (5) posttest. From the results of this activity, an increase in the knowledge of participants in the activity was obtained by 38.6%, based on the posttest to pretest scores. Participants have an idea in determining the type of physical exercise and determining the appropriate dose of physical exercise for each of them.